ISIS and the pornography of violence - Cottee, Simon (Anthem Press, 2019)
'ISIS and the Pornography of Violence' is a collection of iconoclastic essays on ISIS, spanning the four-year period from its ascendancy in late 2014 to its demise in early 2018.